Na trilha do gênero: pentecostalismo e CEBs - (:unkn) unknown (Ministério Público do Estado da Bahia, 2002)
The present study discusses the incorporation of a gender perspective to the study oftwo religious groups that for the last two decades have called the attention of social scientists in Brasil and in other Latin American countries: the Pentecostal groups and the Comunidades Eclesiais de Base (CEBs). Researching relevant studies about these groups, focusing on genderand poverty, the author argues that, although the effort and coherence of recent research are considerable, the deployment of a gender perspective is still very incipient and deserves closer.
On the gender track: Pentecostal Groups ande the Christian Base Communities - CEBS
Keywords: Gênero; Pentecostalismo; Comunidades Eclesiais de Base (CEBs).; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO